Development of a robotic running foot for footwear testing - Nguyen, Thanh Luan (2017)
In footwear testing, the human wear participation method requires a long period and high cost to conduct the experiments and may expose the participants to injury risks. The virtual testing method, which uses computer simulations, faces significant challenges in modeling the complex geometry and realistic testing conditions. Thus, with the ability to stably continuously repeat thousands of testing cycles to reduce the testing time, a third method which uses mechanical devices and automatic systems is preferred in footwear testing. However, available systems do not possess a realistic representation of the human foot, cannot reproduce the wear conditions accurately, and do not mimic properly human running gaits.